TAFSIR SISTEMATIS TERHADAP KESAMAAN FAKTA DAN DASAR HUKUM DALAM GUGATAN PERWAKILAN KELOMPOK DI INDONESIA - Siwi Widiyanti; Heri Hartanto (Verstek, 2025)
This  article  analyzes  the  formal  requirements  of  the  class  action  mechanism,  specifically  the "commonality of  facts or events" and "commonality of  legal grounds," using a systematic interpretation method. The purpose of this article is to identify a singular interpretation of the terms "commonality of facts or events" and "commonality of legal grounds" based on legislation and legally binding court decisions. The findings demonstrate that the formal requirements of "commonality of facts or events" and "commonality of legal grounds" can be met if the plaintiff is able to establish a clear connection between the representative and the group members being represented. The commonality in question includes the type of loss, interest or claim, and the legal grounds invoked.